CEGAH BULLYING SEJAK DINI: EDUKASI EMPATI BAGI SANTRI TPQ MASJID JANNATU ADNIN - Refileli; Dita Hindriani; Ismi Hiba Purnama Sari; Adityo Varza; Restika Putri (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
Bullying is a social issue that remains prevalent in children's educational environments and has negative impacts on students' psychological and social development. Low levels of empathy are one of the factors that trigger bullying behavior. This community service activity aims to enhance students' understanding of bullying and cultivate empathy as an effort to prevent bullying behavior at TPQ Jannatu Adnin Mosque. The method employed was a participatory approach through educational materials delivery, role-playing, group discussions, and reflection on Islamic values regarding mutual respect and compassion. The target participants were children-aged students of TPQ Jannatu Adnin Mosque. The results showed an increase in students' understanding of the forms, impacts, and prevention methods of bullying. Furthermore, students demonstrated heightened awareness of the importance of empathy in peer interactions, evidenced by the emergence of mutual respect, appreciation, and helping behaviors among fellow students. This activity also contributed to creating a safer, more comfortable, and conducive learning environment. Thus, empathy education based on Islamic values can be an effective strategy in preventing bullying and strengthening positive social relationships within the TPQ environment.